Deciphering the influence of structural distortions on the uniaxial magnetic anisotropy of pentagonal bipyramidal Ni(ii) complexes. Issue 77 (6th September 2019) - Dey, Mamon; Mudoi, Prashurya Pritam; Choudhury, Anup; Sarma, Bipul; Gogoi, Nayanmoni
Abstract : Role of structural distortion on the uniaxial magnetic anisotropy of pentagonal bipyramidal Ni(ii ) complexes is explored. A simple strategy to enhance the uniaxial magnetic anisotropy in pentagonal bipyramidal Ni(ii ) complexes is proposed. Abstract : The effect of subtle structural distortions on single ion magnetic anisotropy of pentagonal bipyramidal Ni(ii ) complexes was probed by magnetization measurements and theoretical calculations. Reducing structural distortion on the equatorial pentagonal plane and employing strong field ligands on axial coordination sites dramatically enhance the uniaxial magnetic anisotropy in pentagonal bipyramidal Ni(ii ) complexes.